MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS V SDN 016 BERINGIN JAYA KECAMATAN SINGINGI HILIR KABUPATEN KUANTAN SINGINGI - Juwariyah Juwariyah (JURNAL PAJAR (Pendidikan dan Pengajaran), 2018)
The main problem in learning science in SDN 016 Beringin Jaya is the low learning outcomes of science, seen inthe average student learning outcomes of 65.50. The low learning outcomes caused by the current learningprocess are still teacher dominated (teacher centered) and do not provide access for students to developindependently through discovery in the thinking process. This research is a classroom action research conductedin class V SDN 016 Beringin Jaya. The data used in this study are the activities of teachers and students and theresults of student science learning. The results of the study obtained data on teacher activity in the first cycle ofthe first meeting with a percentage of 55%, the second meeting with a percentage of 67.5%, in the second cycleat the third meeting the percentage of 79.5%, and at the fourth meeting percentage obtained 88.5%. Studentactivity in the first cycle of the 1st meeting was 50%, the second meeting was 68.5%, in the second cycle thethird meeting was 78%, and the fourth meeting was 92%, this proved that the student's activity experiencedenhancement. Student learning outcomes in the initial data obtained an average of 65.5, the daily I test obtainedby the class average of 73, and the second daily test obtained by an average of 80 proved that the use of inquirymethods can improve science learning outcomes.